Aplikasi Kerja Laboratorium Mahasiswa (AKLAM) Di Sekolah Menengah Atas 14 Bone Kabupaten Bone - Andi Jusriana; Sri Ayu Anggita; Ihfa Indira Nurnaifah; Nana Aulia Massakuta; Muhammad Baidhowi Primadi (MAMMIRI: JURNAL PENGABDIAN MASYARAKAT, 2025)
Education is a conscious effort to develop the potential of human resources (HR) through teaching activities. To be able to create conducive teaching and learning activities and be able to develop effective learning outcomes is the task and obligation of teachers as educators. Therefore, teachers directly try to influence, foster and develop students' abilities to become intelligent and skilled people. In essence, practicums are proof of theory, students who refer to theory without any reinforcement through practicums, will The understanding obtained through practicums is usually more memorable and more lasting, because students are directly involved in practicum activities and can prove for themselves the theory given by the teacher. Therefore, the Physics Education Laboratory Assistant Team intends to carry out an activity entitled Student Laboratory Work Application (AKLAM) at the Al-Fityan School Gowa Integrated Islamic Junior High School (SMPIT) - Gowa Regency, which is designed as a creative response to increasing wise values ​​towards educational professionalism towards learning situations. This activity was carried out for four days of implementation by assisting the Head of the Laboratory and the Science Laboratory Manager to improve and complete the administration related to the laboratory. Able to improve students' knowledge about global warming symptoms, junior high school physics practicum, coordination of school practicum equipment data collection, and completion of school laboratory administration as well as improving the quality of practicum learning of the Physics Education laboratory assistant team at UIN Alauddin Makassar S-1 level to comply with national education standards in order to improve the quality of education for Physics Education students of the Faculty of Tarbiyah and Teacher Training, UIN Alauddin Makassar in the future.